EXPLORING THE RELATIONSHIP BETWEEN CHARACTERISTICS OF EXTERNAL COMMUNICATION AND USER EXPERIENCE - CASE OF UPWORK FREELANCING PLATFORM - Šćepanović, Vesna; Šćepanović, Ivan (Poslovna ekonomija, 2025)
The aim of this research was to examine the relation between different communication channels, response times and user experience on the online platform Upwork. The sample included 300 users of the platform who assessed satisfaction, efficiency, and trust in service providers based on interactions through various communication channels (Upwork platform, email, video calls, and instant messaging). The results of the correlation analysis showed a significant correlation between satisfaction and efficiency and between satisfaction and trust, while the relationship between efficiency and trust was also positive and statistically significant. ANOVA showed that there was a significant difference in the average level of customer satisfaction between different communication channels. A regression model for predicting satisfaction based on response time and choice of communication channels showed that shorter response times and the use of video calls significantly contributed to higher satisfaction. The results indicate that choosing the right communication channel and response speed can play a key role in improving the user experience on online platforms.